The Influence of Waste Plastic Fiber on the Characteristics of Light Weight Concrete with Expanded Polystyrene (EPS) as Aggregate (Journal of Engineering, 2023)
This research aims to create lightweight concrete mixtures containing waste from local sources, such as expanded polystyrene (EPS) beads and waste plastic fibers (WPFs), all are cheap or free in the Republic of Iraq and without charge. The modern, rigid, and mechanical properties of LWC were investigated, and the results were evaluated. Three mixtures were made, each with different proportions of plastic fibers (0.4%, 0.8%, 1.2%), in addition to a lightweight concrete mixture containing steak fibers (0.4%, 0.8%, 1.2%), in addition to a lightweight concrete mixture. It contains 20% EPS. The study found that the LWC caused by the addition of WPFs reduced the density (lightweight) of the concrete mixtures because EPS tends to form more blocks, absorb water, and dry the mixture. While the increase in WPF content increased in compressive strength, as the compressive strength of the concrete mix containing (EPS) was only 13.6 MPa, the compressive strength increased to 17.6 MPa when WPFs were added. The addition of plastic also increased the bending resistance, where the bending resistance of the concrete mix containing (EPS) was only 2.26 MPa and increased to 2.66 MPa when (WPFs) were added.